Performance and limitation of mineral oil-based carbon nanotubes nanofluid in transformer application - Md Din, Muhamad Faiz; Hassan, Muhammad Zahir; Suhaimi, Nur Sabrina; Ishak, Mohd Taufiq; Abdul Rahman, Abdul Rashid; Jianli, Wang (Elsevier B.V., 2022)
Transformer oil-based carbon nanotube (CNT) nanofluids which have unique dielectric behaviour, is effective as the posterity insulation fluids that can boost the performance of the transformer as they proposed inspiring, distinctive behaviour compared to existing transformer oil which is widely used in practice namely mineral oils. With this motivation, the effect of AC breakdown voltages for two sonication duration (30 min and 120 min) techniques were applied in producing nanofluids, two different diameter sizes of CNTs (<8 nm and >20 nm) and five different weight concentrations (0.01 g/L to 0.2 g/L) are investigated. The results indicate CNT with a longer sonication process, a smaller diameter and low concentrations of CNT provides the highest breakdown values that gave a huge potential impact on the conventional transformer oil. The Weibull and Normal distributions functions are used in this paper to obtain a successful forecast of the lowest, average, and highest possibility of breakdown rates (1%, 50% and 90%). It figures out that, CNT nanofluid can reach the greatest breakdown efficiency as good insulating oil at 0.01 g/L concentration. To understand the characterization of CNT nanofluids samples in detail, Raman spectroscopy analysis, storage modulus, viscosity and heat flow of mineral oil have been evaluated accordingly as a function of increasing temperature